Unbalanced Treatment Costs of Breast Cancer in China: Implications From the Direct Costs of Inpatient and Outpatient Care in Liaoning Province - Zihua Ma; Gongman Deng; Zhaolin Meng; Yanan Ma; Huazhang Wu (Kerman University of Medical Sciences, 2022)
Background  The increasing incidence of breast cancer and its financial burden highlights the need for controlling treatment costs. This study aimed to assess the direct costs of inpatient and outpatient care for breast cancer patients in Liaoning Province to provide a policy reference for cost containment. Methods  Based on the System of Health Accounts 2011 (SHA 2011), systematic data collection was conducted via multistage stratified cluster random sampling. A total of 1160 health institutions, including 83 hospitals, 16 public health institutions, 120 primary health institutions, and 941 outpatient institutions were enrolled in 2017. A database was established containing 20 035 patient-level medical records from the information system of these institutions. Curative care expenditure (CCE)was calculated, and generalized linear modeling was performed to determine cost-related factors. Results  In 2017, the CCE for breast cancer was approximately CNY 830.19 million (US$122.96 million) in Liaoning province (0.7% of the total health expenditure and 9.9% of cancer- related healthcare costs). Inpatient care costs were estimated to be CNY 617.27 million (US$91.42 million), accounting for 74.4% of the CCE for breast cancer, almost three times as large as outpatient costs (25.6%). The average inpatient and outpatient costs for breast cancer were estimated to be CNY 12 108 (US$1793) and CNY 829 (US$123) per visit. Medication cost was the main cost driver, which comprised 84.0% of the average outpatient cost and 37.2% of the mean inpatient cost. Conclusion  Breast cancer imposes a large economic burden on patients and the social health insurance system. Results show an irrational cost pattern of inpatient and outpatient services, with patients relying excessively on inpatient services for treatment. Promoting outpatient care whenever relevant is conducive to cost containment and rational utilization of resources.